Prevalence of scoliosis among school students in a town in southern Brazil - Nery, Lenice Sberse; Halpern, Ricardo; Nery, Paulo César; Nehme, Karin Passos; Stein, Aírton Tetelbom (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Scoliosis is not a diagnosis, but a description of a structural alteration that occurs in a variety of conditions. Progression of the curvature during periods of rapid growth may result in severe deformity, which may be accompanied by cardiopulmonary compromise. This study had the aims of measuring the prevalence of scoliosis among students in the fifth to eighth school years and investigating possible associations between the presence of scoliosis, body overweight and the weight of school materials. DESIGN AND SETTING: Analytical cross-sectional study developed in the municipality of Carlos Barbosa, Rio Grande do Sul, Brazil. METHODS: A total of 1340 students were evaluated. The variables studied were the prevalence of scoliosis, type of school, location of the school, age, school year, sex, body weight, prevalence of excessive school material weight, height, body mass index (BMI) and spinal alignment measurements. RESULTS: The prevalence of scoliosis was 1.4%; shoulder and scapula asymmetry, 6.6%; forearm and trunk asymmetry, 4.0%; spinal misalignment, 1.9%; Thales triangle asymmetry, 6.4%; body overweight, 19.8%; and carrying of excessively heavy school materials, 27%. The study did not find any statistically significant association between scoliosis and body overweight, or between scoliosis and excessive weight of school materials. CONCLUSIONS: The prevalence of scoliosis in this school-based sample was low. No correlation was found between this clinical condition and the other variables.